2005
DOI: 10.1081/jbc-200055046
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Microwaves and a Temporally Incoherent Magnetic Field on Single and Double DNA Strand Breaks in Rat Brain Cells

Abstract: The effect of a temporally incoherent magnetic field (noise) on microwave-induced DNA single and double strand breaks in rat brain cells was investigated. Four treatment groups of rats were studied: microwave-exposure (continuous-wave 2450-MHz microwaves, power density 1 mW/cm 2 , average whole-body specific absorption rate of 0.6 W/kg), noise-exposure (45 mG), microwave + noise-exposure, and shamexposure. Animals were exposed to these conditions for 2h. DNA single-and doublestrand breaks in brain cells of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 17 publications
2
13
0
1
Order By: Relevance
“…However, since externally imposed electromagnetic 'noise' is spatially coherent, cells are unable to discriminate against it, so it is capable of confusing the biological EMF detection mechanism and inhibits the biological effects induced by applied coherent EMFs. Since then, the 'temporal and spatial coherence hypothesis' of EMF has been supported by many in vitro and in vivo studies [31][32][33][34][35][36][37]. In the present experiment, we found that exposure to a 50-Hz MF for 72 hrs could inhibit the hormone secretion of trophoblasts, while an incoherent ('noise') MF with the same intensity did not.…”
Section: Discussionsupporting
confidence: 61%
“…However, since externally imposed electromagnetic 'noise' is spatially coherent, cells are unable to discriminate against it, so it is capable of confusing the biological EMF detection mechanism and inhibits the biological effects induced by applied coherent EMFs. Since then, the 'temporal and spatial coherence hypothesis' of EMF has been supported by many in vitro and in vivo studies [31][32][33][34][35][36][37]. In the present experiment, we found that exposure to a 50-Hz MF for 72 hrs could inhibit the hormone secretion of trophoblasts, while an incoherent ('noise') MF with the same intensity did not.…”
Section: Discussionsupporting
confidence: 61%
“…Gaps in the sine wave resulted in a reduced response, and interference with the sine wave in the form of superimposed ELF noise also reduced the response [57]. The interfering effect of noise has been shown in the RF range by Lai and Singh [46], who reported that noise interferes with the ability of an RF signal to cause breaks in DNA strands. The decreased effect when noise is added to a signal is yet another indication that EMF energy is not the critical factor in causing a response.…”
Section: The Stress Response and Safety Standardsmentioning
confidence: 94%
“…• As the energy in an EMF stimulus increases, there is an increase in single strand breaks, followed by double strand breaks, suggesting an interaction with EMF at all energy levels [46].…”
Section: Emf-dna Interaction Mechanisms: Electron Transfermentioning
confidence: 99%
“…Although there exist controversies, the 'temporal and spatial coherence hypothesis' of EMF has hitherto been supported by many in vitro and in vivo studies [33][34][35][36][37][38][39]. Based on their studies, Litovitz et al [23,24,40] indicated that a reasonable hypotheses for accounting for thermalnoise fields being ignored by cells or cells can distinguish between external EMF and thermal noise, is that they do exhibit a distinct difference in spatial behaviors.…”
Section: Discussionmentioning
confidence: 99%